2012
DOI: 10.1093/gbe/evs127
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Biosynthesis Gene Evolution Indicates Photosystem Gene Duplication, Not Photosystem Merger, at the Origin of Oxygenic Photosynthesis

Abstract: An open question regarding the evolution of photosynthesis is how cyanobacteria came to possess the two reaction center (RC) types, Type I reaction center (RCI) and Type II reaction center (RCII). The two main competing theories in the foreground of current thinking on this issue are that either 1) RCI and RCII are related via lineage divergence among anoxygenic photosynthetic bacteria and became merged in cyanobacteria via an event of large-scale lateral gene transfer (also called "fusion" theories) or 2) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 146 publications
(217 reference statements)
8
79
0
Order By: Relevance
“…This pattern is also observed in Fig. 1 which also contained non-phototrophic representatives of the same phyla and it is consistent with previous phylogenetic (Quaiser et al 2003, Bryant et al 2012, Sousa et al 2013, Greening et al 2015, Cardona 2016a) and phylogenomic (Ciccarelli 2006, Dutilh et al 2008, Wu and Eisen 2008, Ward et al 2009, Jun et al 2010, David and Alm 2011, Rinke et al 2013, Segata et al 2013, Marin et al 2017) studies that have repeatedly confirmed the Acidobacteria as a sister clade of the Proteobacteria, or branching within the Proteobacteria as a sister clade of the deltaproteobacteria. At the same time, the nearness of the Chlorobi to Acidobacteria and Proteobacteira is also consistent with the ChlorobiBacteroidetes-Fibrobacterere supergroup bifurcating prior to the radiation of the Proteobacteria (Wu and Eisen 2008, Jun et al 2010, David and Alm 2011, Segata et al 2013, Marin et al 2017.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This pattern is also observed in Fig. 1 which also contained non-phototrophic representatives of the same phyla and it is consistent with previous phylogenetic (Quaiser et al 2003, Bryant et al 2012, Sousa et al 2013, Greening et al 2015, Cardona 2016a) and phylogenomic (Ciccarelli 2006, Dutilh et al 2008, Wu and Eisen 2008, Ward et al 2009, Jun et al 2010, David and Alm 2011, Rinke et al 2013, Segata et al 2013, Marin et al 2017) studies that have repeatedly confirmed the Acidobacteria as a sister clade of the Proteobacteria, or branching within the Proteobacteria as a sister clade of the deltaproteobacteria. At the same time, the nearness of the Chlorobi to Acidobacteria and Proteobacteira is also consistent with the ChlorobiBacteroidetes-Fibrobacterere supergroup bifurcating prior to the radiation of the Proteobacteria (Wu and Eisen 2008, Jun et al 2010, David and Alm 2011, Segata et al 2013, Marin et al 2017.…”
Section: Resultssupporting
confidence: 91%
“…However, recent detailed analysis of the phylogeny of RC proteins indicates that HGT of RCs to an ancestral nonphotosynthetic cyanobacterium from anoxygenic phototrophic bacteria is unlikely (Cardona 2016b); furthermore, the evolution of RC proteins shows that the last common ancestor to all phototrophic bacteria had already evolved Type I and Type II RC proteins from an earlier gene duplication event (Sousa et al 2013, Harel et al 2015. In addition, it has been argued that the evolution of the structural complexity of PSII and the origin of the oxygenevolving manganese cluster can only be explained if both types of RC had been evolving in cooperation since the dawn of photosynthesis and that water oxidation might therefore have occurred at a far earlier stage of evolution that previously thought (Cardona 2016b(Cardona , 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How they synthesize chlorophyll remains a mystery, given that all known chlorophyll-synthesizing pathways use protoporphyrin as an intermediate. Such cases are exceedingly rare: Of 72 photosynthetic organisms included in this study (23) (Dataset S1), only three species from two major taxonomic groups fall into this category, namely, Heliobacterium modesticaldum of the Grampositive photosynthetic heliobacteria (44,45) and Roseiflexus sp. RS-1 and Roseiflexus castenholzi of green nonsulfur bacteria (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenic photosynthesis arose from (after) anoxygenic pho-tosynthesis, on that all biologists agree, but whether the two photosystems of cyanobacteria became divergent in one and the same genome or in different genomes is more debated (Hohmann-Marriott and Blankenship 2011), whereby lack of a deep split in chlorophyll biosynthesis that would mirror the deep spilt of the photosystems is lacking (Sousa et al 2013a), suggesting that the two photosystems arose and diverged within the same cell (Allen 2005). The evolution of photosynthetic electron transport chains (with chlorophylls) requires that basic biochemical components like cytochromes and quinones were in place, meaning that respiratory electron transport chains (with heme) preceded photosynthetic electron transport chains (and O 2 ) in evolution.…”
Section: Physiology In Addition To Treesmentioning
confidence: 99%